Identification of Candidate Olfactory Genes in Scolytus schevyrewi Based on Transcriptomic Analysis - Zhu, Xiaofeng; Xu, Bingqiang; Qin, Zhenjie; Kader, Abudukyoum; Song, Bo; Chen, Haoyu; Liu, Yang; Liu, Wei (Frontiers in Physiology, 2021)
The bark beetle, Scolytus schevyrewi, is an economically important pest in China that causes serious damage to fruit industry, particularly in Xinjiang Province. Chemical signals play an important role in the behavior of most insects, accordingly, eco-friendly traps can be used to monitor and control target pests in agriculture. In order to lay a foundation for future research on chemical communication mechanisms at the molecular level, we generate antennal transcriptome databases for male and female S. schevyrewi using RNA sequencing (RNA-seq) analysis. By assembling and analyzing the adult male and female antennal transcriptomes, we identified 47 odorant receptors (ORs), 22 ionotropic receptors (IRs), 22 odorant-binding proteins (OBPs) and 11 chemosensory proteins (CSPs). Furthermore, expression levels of all the candidate OBPs and CSPs were validated in different tissues of male and female adults by semi-quantitative reverse transcription PCR (RT-PCR). ScosOBP2 and ScosOBP18 were highly expressed in female antennae. ScosCSP2, ScosCSP3 and ScosCSP5 were specifically expressed in the antennae of both males and females. These results provide new potential molecular targets to inform and improve future S. schevyrewi management strategies.